2016
DOI: 10.3389/fpls.2016.00738
|View full text |Cite
|
Sign up to set email alerts
|

Split Nitrogen Application Improves Wheat Baking Quality by Influencing Protein Composition Rather Than Concentration

Abstract: The use of late nitrogen (N) fertilization (N application at late growth stages of wheat, e.g., booting, heading or anthesis) to improve baking quality of wheat has been questioned. Although it increases protein concentration, the beneficial effect on baking quality (bread loaf volume) needs to be clearly understood. Two pot experiments were conducted aiming to evaluate whether late N is effective under controlled conditions and if these effects result from increased N rate or N splitting. Late N fertilizers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
69
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 33 publications
18
69
0
7
Order By: Relevance
“…Several studies have shown that the increase in flour protein content resulting from N application can lead to changes in protein composition (Gupta, Khan, & MacRitchie, 1993;Saint Pierre et al, 2008;Xue et al, 2016). Studies reported previously were based on various timings of N fertilization, when the application at an early stage increased yield, and at a later stage increased the amount of protein, and improved the baking quality properties (Jia, Fabre, & Aussenac, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the increase in flour protein content resulting from N application can lead to changes in protein composition (Gupta, Khan, & MacRitchie, 1993;Saint Pierre et al, 2008;Xue et al, 2016). Studies reported previously were based on various timings of N fertilization, when the application at an early stage increased yield, and at a later stage increased the amount of protein, and improved the baking quality properties (Jia, Fabre, & Aussenac, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the presence of subunit 1Bx7 was reported to contribute to good wheat quality (Lukow, Forsyth, & Payne, 1992). Furthermore, nitrogen (N) management can influence the metabolic activity within the plant and the protein composition within the kernel (Garcia-Molina & Barro, 2017;Xue et al, 2016). Environmental conditions, such as nutrient deficiency, tend to increase the relative concentration of gliadins and decrease the relative concentration of glutenin in the kernel (Johansson, Prieto-Linde, & Svensson, 2004;Zörb, Ludewig, & Hawkesford, 2018).…”
mentioning
confidence: 99%
“…Extraction of whole‐meal flour storage‐protein fractions was performed stepwise according to Wieser and Seilmeier (1998) with some modifications ( Xue et al, 2016). First, albumins and globulins were extracted from 100 mg whole‐meal flour with extraction buffer (0.4 mol L −1 NaCl, 67 mmol L −1 Na 2 HPO 4 , 7.7 mmol L −1 KH 2 PO 4 , pH 7.6).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, two pot experiments regarding late N fertilization influences on protein and quality of two wheat cultivars were conducted ( Xue et al, 2016). Results showed that late N application (applying part of the overall N fertilizer at late growth stage of wheat without additional N fertilizer input) at late boot stage improved loaf volume of wheat flour mainly through the effect of N splitting on the proportions of gliadins and glutenins (% total protein) and the relative abundance of certain high molecular weight glutenin subunits (HMW‐GS).…”
Section: Introductionmentioning
confidence: 99%
“…Growth in protein and gluten contents are linked, which correlates positively with the physical properties of dough. Meanwhile, the biosynthesis of high-polymeric gluten fractions enhances which make dough more elastic [32][33][34]. Late N-fertilization and foliar feeding are especially beneficial.…”
Section: Dynamicsmentioning
confidence: 99%